2013
DOI: 10.1371/journal.pone.0058099
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Health Problems Associated with Increased HIV Risk Behavior among Men Who Have Sex with Men in Nepal: A Cross-Sectional Survey

Abstract: BackgroundMen who have sex with men (MSM) are marginalized, hidden, underserved and at high risk for HIV in Nepal. We examined the association between MSM sub-populations, psychosocial health problems and support, access to prevention and non-use of condoms.MethodsBetween September-November of 2010, a cross-sectional survey on HIV-related risk behavior was performed across Nepal through snowball sampling facilitated by non-governmental organizations, recruiting 339 MSM, age 15 or older. The primary outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 36 publications
5
53
1
Order By: Relevance
“…This finding is consistent with studies in India and neighboring Nepal that have found condom use among MSM populations to be low (Brahmam et al, 2008;Dandona et al, 2005;Deuba et al, 2013). For example, Deuba et al (2013) studied MSM in Nepal and found that 78.0% did not use condoms at last anal sex with another male partner, compared to 35% having not used a condom at last sex with a female partner. Dandona et al (2005) documented the main reasons for not using condoms at last anal sex with a male partner among a large sample (n = 6661) of MSM in Andhra Pradesh (India), including: (1) dislike of condoms (27.3%),…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with studies in India and neighboring Nepal that have found condom use among MSM populations to be low (Brahmam et al, 2008;Dandona et al, 2005;Deuba et al, 2013). For example, Deuba et al (2013) studied MSM in Nepal and found that 78.0% did not use condoms at last anal sex with another male partner, compared to 35% having not used a condom at last sex with a female partner. Dandona et al (2005) documented the main reasons for not using condoms at last anal sex with a male partner among a large sample (n = 6661) of MSM in Andhra Pradesh (India), including: (1) dislike of condoms (27.3%),…”
Section: Discussionsupporting
confidence: 89%
“…Engaging in risk and unprotected sex has been documented as a coping strategy to deal with stress in migrant (Du & Li, 2015)and non-migrant populations (Brody, Chen, & Kogan, 2010; Deuba et al, 2013; Folkman, Chesney, Pollack, & Phillips, 1992; Muñoz-Laboy, Severson, & Bannan, 2014). The research findings described in the previous sections suggest a potential mechanism by which poor mental health mediates the association between migration stress and sexual risk behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The poor outcomes in the initial few months after ART initiation might be due to delayed diagnosis and/or treatment, and explained by the fact that 60.5% of patients had advanced disease (CD4 count <200 cells/mm 3 ) and 37.2% of patients had advanced clinical symptoms (WHO clinical stage III or IV) at the time of treatment initiation. Several factors such as HIV-related stigma and discrimination [22] may have played a vital role in delaying diagnosis and/or treatment. Moreover, the lack of proper screening diagnostic facilities for opportunistic infections and the limited availability of prophylaxis may have also increased mortality [19,21].…”
Section: Discussionmentioning
confidence: 99%